2006
DOI: 10.4081/ijas.2006.129
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in three Italian beef cattle breeds derived from pedigree information

Abstract: The aim of the present work was to estimate genetic variability in Chianina (CH), Marchigiana (MC) and Romagnola (RO) breeds using pedigree information. Different approaches based on probability of identity-by-descent (effective population size through an increase in inbreeding Ne) or probability of gene origin (total number of founders f, effective number of founders fe, ancestors fa and founder genomes fg) were used. Reference populations were defined using female animals born between 1996 and 2000 where bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
4
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 16 publications
(30 reference statements)
3
17
4
6
Order By: Relevance
“…Only 13 of these ancestors explained 50% of the genetic background of this population. In the study of Bozzi et al (2006) on Italian Marchigiana cattle, the number of ancestors explaining 50% of the gene pool was greater than in the present work (21). Because the animals of the present study probably descended from those studied by Bozzi et al (2006), this estimate is indeed expected to be reduced in Brazil.…”
Section: Population Structure and Inbreedingcontrasting
confidence: 45%
See 3 more Smart Citations
“…Only 13 of these ancestors explained 50% of the genetic background of this population. In the study of Bozzi et al (2006) on Italian Marchigiana cattle, the number of ancestors explaining 50% of the gene pool was greater than in the present work (21). Because the animals of the present study probably descended from those studied by Bozzi et al (2006), this estimate is indeed expected to be reduced in Brazil.…”
Section: Population Structure and Inbreedingcontrasting
confidence: 45%
“…In the study of Bozzi et al (2006) on Italian Marchigiana cattle, the number of ancestors explaining 50% of the gene pool was greater than in the present work (21). Because the animals of the present study probably descended from those studied by Bozzi et al (2006), this estimate is indeed expected to be reduced in Brazil. Similar results have been reported by Gutiér-rez et al (2003), Faria et al (2009), andPeixoto et al (2010) for different cattle breeds.…”
Section: Population Structure and Inbreedingcontrasting
confidence: 45%
See 2 more Smart Citations
“…For Danish Holstein, Danish Jersey and Danish Red populations, generation intervals between 4.6 and 5.2 years have been reported (Sorensen et al, 2005). Most of the Spanish beef breeds studied by Gutierrez et al (2003) had average generation intervals of between 3.7 and 5.5 years; and Bozzi et al (2006) reported generation intervals ,5.35 for three Italian beef breeds. The structure of the pedigree at the Interbull Centre, which is built primarily on the male side of the pedigree, can explain, in part, the long generation interval in our material: in that material the females without offspring are missing, and therefore the dam-daughter and sire-daughter generation intervals are overestimated.…”
Section: Discussionmentioning
confidence: 99%